Multiple Criteria Decision Making, Multiattribute Utility Theory: Recent Accomplishments and What Lies Ahead - Wallenius, Jyrki; Dyer, James S.; Fishburn, Peter C.; Steuer, Ralph E.; Zionts, Stanley; Deb, Kalyanmoy (Management Science, 2008)
This paper is an update of a paper that five of us published in 1992. The areas of multiple criteria decision making (MCDM) and multiattribute utility theory (MAUT) continue to be active areas of management science research and application. This paper extends the history of these areas and discusses topics we believe to be important for the future of these fields.